1990
DOI: 10.1007/bf01612998
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nucleolar organizer regions by automatic image analysis in breast cancer: correlation with DNA content, proliferation rate, receptor status and histopathological grading

Abstract: The value of automatic image analysis in the investigation of nucleolus regions (AgNOR) has been examined in tissue sections of 52 malignant and 30 benign breast lesions. Determination of the AgNOR number per cell alone revealed a considerable overlap between benign (range 1.2-3.8) and malignant specimens (range 1.5-16.2). They differed however, highly significantly (P less than 0.001) in their AgNOR sizes. In benign breast disorders the mean AgNOR area per tumour ranged from 0.22 microns2 to 1.07 microns2 (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
6

Year Published

1995
1995
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 39 publications
0
19
0
6
Order By: Relevance
“…An inverse ratio between AgNOR number and size was observed in their study. Ruschoff 19 also found such a ratio between AgNOR number and area. As shown in Table I and Figure 1, benign mesothelial cells revealed a low AgNOR count (mean, 1.92) but slightly enlarged single dots, whereas malignancies exhibited a greater number but smaller, irregular AgNOR dots (Figure 2).…”
Section: Discussionmentioning
confidence: 84%
“…An inverse ratio between AgNOR number and size was observed in their study. Ruschoff 19 also found such a ratio between AgNOR number and area. As shown in Table I and Figure 1, benign mesothelial cells revealed a low AgNOR count (mean, 1.92) but slightly enlarged single dots, whereas malignancies exhibited a greater number but smaller, irregular AgNOR dots (Figure 2).…”
Section: Discussionmentioning
confidence: 84%
“…However, for reasons already discussed above, our results are difficult to compare with findings of previous investigations. All studies performed by means of computer-aided image analysing systems [11,28,51] showed a significant correlation of various AgNOR parameters with steroid hormone receptor expression and tumor grade. This could be confirmed in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…Biesterfeld et al (1995) showed that MFC had a greater prognostic impact than the Bloom-Richardson score in their series of 104 ductal breast carcinomas. Data concerning correlations between Ki-67 and other cell kinetics markers in breast cancer are controversial: a significant correlation to argyrophilic nucleolus organizing regions (AgNOR) has been reported (Dervan et al, 1989;Ruschoff et al, 1990); however, no significant correlation between Ki-67 and the proliferating cell nuclear antigen (PCNA) has been found (Gasparini et al, 1994). For Ki-67 as well as Sphase fraction, a significant correlation with the thymidine labelling index has been reported (McDivitt et al, 1986;Kamel et al, 1989).…”
Section: Discussionmentioning
confidence: 99%